Abses Iliopsoas Akibat Tuberkulosis: Sebuah Laporan Kasus - Sari, Desty Gusti; Imanuela, Rosatya; Resultanti, Resultanti (Jurnal Penyakit Dalam Indonesia, 2024)
Psoas abscess is a rare condition with an unclear clinical presentation where there is a collection of pus in the iliopsoas compartment. The most common cause of an iliopsoas abscess is infection with Staphylococcus aureus. Mycobacterium tuberculosis rarely causes psoas abscesses, with an incidence of about 10–30% of extrapulmonary tuberculosis and only 3% of tuberculosis in general. Psoas abscesses due to tuberculosis is quite rare and has non-specific symptoms, so it sometimes causes a late diagnosis. This case study reports on male aged 43-year-old patient who had previously been diagnosed with spondylitis tuberculosis (TBC) and complained of pain accompanied by swelling in both legs and scrotum. A diagnostic examination was performed. Computed tomography (CT) scan abdomen contrast found an abscess on the iliopsoas, so the patient was treated with anti-TBC drugs and percutaneous drainage for abscess evacuation. Clinical and laboratory improvements were obtained after the therapeutic action was carried out.